Naturally Occurring Radioactive Materials in Bracelets and Necklaces: Radiological Risk Evaluation - Halmat Jalal Hassan (MDPI AG, 2021)
A particular category of jewelry is one involving bracelets and necklaces that are deliberately made to contain naturally occurring radioactive material (NORM)—purveyors making unsubstantiated claims for health benefits from the release of negative ions. Conversely, within the bounds of the linear no-threshold model, long-term use presents a radiological risk to wearers. Evaluation is conducted herein of the radiological risk arising from wearing these products and gamma-ray spectrometry is used to determine the radioactivity levels and annual effective dose of 15 commercially available bracelets (samples B1 to B15) and five necklaces (samples N16 to N20). Various use scenarios are considered; a Geant4 Monte Carlo (Geant4 MC) simulation is also performed to validate the experimental results. The dose conversion coefficient for external radiation and skin equivalent doses were also evaluated. Among the necklaces, sample N16 showed the greatest levels of radioactivity, at 246 ± 35, 1682 ± 118, and 221 ± 40 Bq, for 238U, 232Th, and 40K, respectively. For the bracelets, for 238U and 232Th, sample B15 displayed the greatest level of radioactivity, at 146 ± 21 and 980 ± 71 Bq, respectively. N16 offered the greatest percentage concentrations of U and Th, with means of 0.073 ± 0.0002% and 1.51 ± 0.0015%, respectively, giving rise to an estimated annual effective dose exposure of 1.22 mSv, substantially in excess of the ICRP recommended limit of 1 mSv/year.